Appraisal of the socio-economic status of fishers among the different sectors in Kerala, south-west coast of India - Salim, Shyam S.; Narayanakumar, R.; Sathiadas, R.; Manjusha, U.; Antony, Bindu (Indian Journal of Fisheries, 2017)
The present study assessed the levels of literacy, health, income and livelihood security of fisher households across different fisheries sectors in Kerala. Primary data collected across 567 households during January to December, 2011were used for the study. The general trend in Kerala shows that majority of the fisherfolk were of the age group 36-55, with a small family norm and high literacy rate. The marine capture sector has the highest annual income in comparison with other sectors but registered higher indebtedness. While the highest income from non-fishery activity was from labour Â followed by business, other sectors and agriculture. The study revealed that the fishers spend their major share of income towards food expenditure. Inspite of the income from various sources, majority of the households are swamped with debts which make them to rely on private money lenders for sustaining their living standards. The study is a cross sectoral analysis of the fisher households in Kerala and provides a base for implementing developmental plans for the betterment of the fishing community.